2018
DOI: 10.1089/ars.2017.7175
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Environmental Risk Factors, Noise-Induced Hearing Loss, and Mental Stress

Abstract: We conclude that, even though in some cases important advances have been made regarding close correlations between specific miRNAs and biological responses to environmental risk factors, a need for prospective large-cohort studies is likely necessary to establish causative roles. Antioxid. Redox Signal. 28, 773-796.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 234 publications
(224 reference statements)
2
46
0
Order By: Relevance
“…epigenetic or microRNA) changes of signalling cascades leading to an imbalance between ROS production and detoxification. 30 Also central effects have been described consisting of autonomic imbalance and hypothalamic–pituitary–adrenal axis activation that is partially based on the lung arc reflex as well as potential crossing of the blood–brain barrier by reactive gases, ultrafine particles and soluble, PM surface-bound compounds such as transition metals, endotoxins and reactive (photo-activated) quinones/aldehydes ( Figure 3 ). 26 , 31 …”
Section: Pathophysiological Insights Into Mechanisms Of Air Pollutionmentioning
confidence: 99%
“…epigenetic or microRNA) changes of signalling cascades leading to an imbalance between ROS production and detoxification. 30 Also central effects have been described consisting of autonomic imbalance and hypothalamic–pituitary–adrenal axis activation that is partially based on the lung arc reflex as well as potential crossing of the blood–brain barrier by reactive gases, ultrafine particles and soluble, PM surface-bound compounds such as transition metals, endotoxins and reactive (photo-activated) quinones/aldehydes ( Figure 3 ). 26 , 31 …”
Section: Pathophysiological Insights Into Mechanisms Of Air Pollutionmentioning
confidence: 99%
“…epigenetic or microRNA) changes of signalling cascades leading to an imbalance between ROS production and detoxification. 30 Also central effects have been described consisting of autonomic imbalance and hypothalamic-pituitaryadrenal axis activation that is partially based on the lung arc reflex as well as potential crossing of the blood-brain barrier by reactive gases, ultrafine particles and soluble, PM surface-bound compounds such as transition metals, endotoxins and reactive (photo-activated) quinones/aldehydes (Figure 3). 26,31 Animal studies A variety of different approaches have been employed to study the effects of air pollution in the experimental context.…”
Section: Pathophysiological Insights Into Mechanisms Of Air Pollutionmentioning
confidence: 99%
“…Currently, studies on miRNAs and hearing loss have demonstrated that these miRNAs can be used as potential biomarkers to indicate NIHL [15,23]. In a study involving miRNA-15a-1 and miRNA-18a in the development of the ear structure of zebrafish, it was found that the number of hair cells in the deformed body decreased, and the inner ear structure was abnormal [24].…”
Section: Discussionmentioning
confidence: 99%